Centring lived experiences in food environment research: A methodological framework and application in Colombo, Sri Lanka - Salm, Leah; Gooneratne, Anisha; Perera, Iromi; Gordon, Jessica; Meeker, Jessica; Nisbett, Nicholas (Elsevier, 2025)
Poor-quality diets and diet-related non-communicable diseases are a pressing global issue. Food environments, where everyday food choices intersect with broader food system dynamics, have emerged as a key policy intervention point. However, these environments are complex, shaped by physical, social, cultural, and political factors, and require insights from diverse stakeholders, especially those who provide and consume food.